Contrasting Patterns of Clinal Genetic Diversity and Potential Colonization Pathways in Two Species of Western Atlantic Fiddler Crabs - Laurenzano, Claudia (PLoS One, 2016)
Fiddler crabs (Brachyura, Ocypodidae), like many other marine organisms, disperse via planktonic larvae. A lengthy pelagic larval duration is generally assumed to result in genetic connectivity even among distant populations. However, major river outflows, such as of the Amazon or Orinoco, or strong currents may act as phylogeographic barriers to ongoing gene flow. For example, the Mona Passage, located between Puerto Rico and Hispaniola, has been postulated to impair larval exchange of several species. In this study, Cox1 mtDNA data was used to analyze population genetic structure of two fiddler crab species from the western Atlantic, comparing the continental coastline and Caribbean islands. The results indicate genetic homogeneity in Minuca rapax among Atlantic (continental) populations (Suriname, Brazil), whereas Caribbean populations show significantly restricted gene flow among the constituent islands and towards continental populations. Our data support the hypothesis of the Mona Passage hindering larval exchange. Contrastingly, Caribbean Leptuca leptodactyla populations appear to be devoid of detectable variation, while Atlantic-continental (i.e. Brazilian) populations show much higher haplotype and nucleotide diversities and display slight genetic differentiation among populations within the Atlantic region, though not statistically significant. Both species show a pronounced divergence between regions, supporting the presence of a phylogeographic barrier.